Determinants of decision in event participation perception of event organizer - Sudarsi Sudarsi; Nining Yuniati (Universitas Merdeka Malang, 2022)
The study is aimed to find out the variable effects of accessibility, organizer, accommodation, venue, and price through event participation decisions. The research sample of the population was the event organizer in Yogyakarta and Central Java, however, the data was conducted through a random sampling technique by 100 respondents. There are five variables tested that are thought to have an influence on participants' decisions in participating in the event, namely accessibility (X1), organizer (X2), accommodation (X3), venue (X4), and price perceived (X5). By classical assumption test, it was found that the five variables had a significant influence on the decision to participate in the event